2017
DOI: 10.1002/adem.201600721
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Short Fatigue Crack Propagation in a 3D Experimental Microstructure

Abstract: International audienceA three dimensional simulation of short fatigue crack propagation in a polycrystalline microstructure using a crystal plasticity finite element model is carried out. The experimental microstructure which contains several hundreds grains, was obtained via diffraction contrast tomography. A step-by-step short fatigue crack growth model based on capturing the plastic activity at the crack tip is used. Technical details are given and discussed in light of the compromise needed to perform such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…On the contrary, most experimental approaches usually rely on large experimental samples that may be considered RVEs. Some experimental approaches [21,22] have considered SVE by restricting the active volume with the introduction of an artificial crack. However, these analyses do not describe the incidence of small volumes on the natural nucleation of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, most experimental approaches usually rely on large experimental samples that may be considered RVEs. Some experimental approaches [21,22] have considered SVE by restricting the active volume with the introduction of an artificial crack. However, these analyses do not describe the incidence of small volumes on the natural nucleation of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…The model showed convergence to linear elastic fracture mechanics, but a direct comparison with 3D data was not performed due to the lack of experimental data. Li et al (2014) and Proudhon et al (2017) were among the first in trying to reproduce an experimentally observed SC utilizing a FIP as the driving force for the crack advancement. Data was collected utilizing a technique known as 3D x-ray tomography for small crack and microstructure (3DXTSM, Herbig et al, 2011), which provides high-resolution images of SCs propagating into a polycrystalline aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, CP was combined with adaptive remeshing to achieve either straight or zigzag paths based on single-or double-slip behaviour of the material [27][28][29]. The damage indicator used in these papers was a combination of normal stress, resolved shear stress, and shear strain of each slip system.…”
Section: Introductionmentioning
confidence: 99%